2009
DOI: 10.3949/ccjm.76.s2.10
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac sympathetic denervation preceding motor signs in Parkinson disease

Abstract: There is substantial interest in identifying biomarkers to detect early Parkinson disease (PD). Cardiac noradrenergic denervation and attenuated baroreflex-cardiovagal function occur in de novo PD, but whether these abnormalities can precede PD has been unknown. Here we report the case of a patient who had profoundly decreased left ventricular myocardial 6-[ 18 F]fluorodopamine-derived radioactivity and low baroreflex-cardiovagal gain, 4 years before the onset of symptoms and signs of PD. The results lead us t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…Previous investigators have observed ABR dysfunction in PD, which may precede the development of behavioral and motor symptoms of PD (14,15). These clinical observations provided the impetus for our current investigation of the potential for SAD-induced ABR dysfunction to cause PD.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous investigators have observed ABR dysfunction in PD, which may precede the development of behavioral and motor symptoms of PD (14,15). These clinical observations provided the impetus for our current investigation of the potential for SAD-induced ABR dysfunction to cause PD.…”
Section: Discussionmentioning
confidence: 82%
“…For example, orthostatic hypotension is a common symptom of cardiovascular dysfunction in patients with PD, which appears to arise from a combination of vasomotor-, cardiac sympathetic-, and baroreflex-dysfunction (13). Importantly, attenuated baroreflex function in PD may even precede the behavioral and motor symptoms of PD (14,15). To our knowledge, no studies have focused on the effects of ABR dysfunction on behavior and motor function.…”
Section: Introductionmentioning
confidence: 96%
“…A way to test the catecholaldehyde hypothesis would be to determine if inhibiting MAO-A slows catecholaminergic neurodegeneration, as assessed by neuroimaging (Goldstein et al, 2007) or neurochemical (Goldstein et al, 2012a) biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, neuroimaging evidence of cardiac sympathetic denervation has been found in all PD patients with orthostatic hypotension (PD+OH; also known as PD with postural hypotension) analyzed (3); however, a substantial proportion of PD patients without OH (PD-No-OH) lack evidence of such denervation and have near-normal myocardial neuron uptake of the sympathetic imaging agent 6-[ 18 F]-dopamine ( 18 F-DA) (4). Since striatal dopaminergic and cardiac sympathetic denervation develop over the course of several years (5,6), understanding the underlying pathologic processes could allow for early identification of individuals at risk for PD and therefore provide an opportunity for neuroprotective intervention.…”
Section: Introductionmentioning
confidence: 99%